2007
DOI: 10.1039/b700719a
|View full text |Cite
|
Sign up to set email alerts
|

Assessing depleted uranium (DU) contamination of soil, plants and earthworms at UK weapons testing sites

Abstract: Depleted uranium (DU) weapons testing programmes have been conducted at two locations within the UK. An investigation was therefore carried out to assess the extent of any environmental contamination arising from these test programmes using both alpha spectrometry and mass spectrometry techniques. Uranium isotopic signatures indicative of DU contamination were observed in soil, plant and earthworm samples collected in the immediate vicinity of test firing points and targets, but contamination was found to be l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 28 publications
1
37
0
2
Order By: Relevance
“…Little is known about the geochemical behavior and fractionation of U in polluted soils. Several authors have investigated the biogeochemical fate of DU in polluted environments [6,[38][39][40] but none of these authors focused on forest soils. Results from sequential extraction for U in forest soils were published by Virtanen et al [41] but these authors studied various size fractions of four different mineral soils from an unpolluted boreal area.…”
Section: Distribution and Mobility Of Metals In Soilsmentioning
confidence: 99%
“…Little is known about the geochemical behavior and fractionation of U in polluted soils. Several authors have investigated the biogeochemical fate of DU in polluted environments [6,[38][39][40] but none of these authors focused on forest soils. Results from sequential extraction for U in forest soils were published by Virtanen et al [41] but these authors studied various size fractions of four different mineral soils from an unpolluted boreal area.…”
Section: Distribution and Mobility Of Metals In Soilsmentioning
confidence: 99%
“…Recently, growing concern has arisen regarding the DU released from munitions employed in conflict areas, such as the Middle East and Kosovo (Bem and Bou-Rabee, 2004;Jia et al, 2004Jia et al, , 2005Di Lella et al, 2005), as well as weapons testing sites (Bleise et al, 2003;McClain et al, 2001;Oliver et al, 2007Oliver et al, , 2008. While chemical toxicity of natural U is considered to be identical to DU, radiological toxicities are different, since DU emits around 40% less radiation than natural U (Craft et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…In uranium mining areas, ingestion has been found to range between 13 and 18 μg/day (ATSDR, 1999;Harley, 1999). A number of studies have demonstrated increased uranium levels in the soil in these sites several years after the conflict (Sansone et al, 2001a,b;Danesi et al, 2003a,b;Durante and Pugliese, 2003;Bem and Bou-Rabee, 2004;Di Lella et al, 2004, 2005Jia et al, 2005Jia et al, , 2006Oliver et al, 2007Oliver et al, , 2008aZunic et al, 2008;Giovanetti et al, 2010). A number of studies have demonstrated increased uranium levels in the soil in these sites several years after the conflict (Sansone et al, 2001a,b;Danesi et al, 2003a,b;Durante and Pugliese, 2003;Bem and Bou-Rabee, 2004;Di Lella et al, 2004, 2005Jia et al, 2005Jia et al, , 2006Oliver et al, 2007Oliver et al, , 2008aZunic et al, 2008;Giovanetti et al, 2010).…”
Section: Ingestionmentioning
confidence: 99%